Thought of Abû al-Ḥasan Alî al-Ḥasanî al-Nadwî against the Setbacks of Muslims - Monang, Sori (Budapest International Research and Critics University, 2020)
The aims of this study is to find out the thought of Abû al-Ḥasan Alî al-Ḥasanî al-Nadwî against the Setbacks of Muslims. The resut shows that there are several ways that Muslims can do to achieve progress; among them is, re-implementing the caliphate system, with the Islamic caliphate pattern, according to al-Nadwî, the glory of Islam will return to the same as in the time of the Prophet. In addition, the role of the Ulama must be the front guard that becomes central in society, also the Ulama must maintain their knowledge and practice it, and get a strong disposition among the people as a source of reference in seeing and deciding cases in accordance with the Islamic concept which is rahmat li al-Alamin.